2019
DOI: 10.1109/access.2019.2917008
|View full text |Cite
|
Sign up to set email alerts
|

Performance Degradation Prediction and Reliability Evaluation of Rubber Aging in Natural Environment Under Alternating Cyclic Thermal Load

Abstract: With a focus on predicting the degradation of rubber performance in the natural environment and evaluating its reliability, the distribution law of accelerated aging life is analyzed through the accelerated aging test of hot oxygen. A Weibull distribution model is then established to verify the consistency of the accelerated aging mechanism. Through the constant stress accelerated aging test data, the aging characteristics of the rubber under alternating thermal stress load in the natural environment are infer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Dating back to the 1880s, the Swedish scientist Arrhenius first proposed the Arrhenius relationship when he found that chemical reaction rates were approximately proportional to the applied temperature after conducting massive experiments. Since then, this physics-based acceleration model has received wide applications for incorporating the temperature stress in accelerated degradation modeling, and a large number of products are designed to damage by thermal stress, e.g., rubber [9], batteries [42], carbon film resistors [58], light-emitting diodes (LED) [59], and electrical connectors [35], [60]. In these cases, the Arrhenius relationship or its logarithmic-linear forms are the best choice for acceleration modeling [56], [61].…”
Section: A: Physical Acceleration Modelmentioning
confidence: 99%
See 4 more Smart Citations
“…Dating back to the 1880s, the Swedish scientist Arrhenius first proposed the Arrhenius relationship when he found that chemical reaction rates were approximately proportional to the applied temperature after conducting massive experiments. Since then, this physics-based acceleration model has received wide applications for incorporating the temperature stress in accelerated degradation modeling, and a large number of products are designed to damage by thermal stress, e.g., rubber [9], batteries [42], carbon film resistors [58], light-emitting diodes (LED) [59], and electrical connectors [35], [60]. In these cases, the Arrhenius relationship or its logarithmic-linear forms are the best choice for acceleration modeling [56], [61].…”
Section: A: Physical Acceleration Modelmentioning
confidence: 99%
“…In the laboratory, the constant current is usually used to accelerate the degradation process of LED [2], [98], and film capacitors [3]. More applications of constant-stress loading can be seen in degradation analysis of sealing rubber rings [9], electronic connectors [61], and crack growth [99]. However, the variability of degradation models (e.g., the regression-based approach [100]- [102] and stochastic process [37], [103]) makes ADT planning complicated, especially when environmental stress factors, individual differences, and measurement errors, are considered.…”
Section: ) the Optimal Design Of Csadtmentioning
confidence: 99%
See 3 more Smart Citations